Clear cell Cystic Variant of Calcifying Epithelial Odontogenic Tumor - Urias Barreras, Cynthia M. (Springer US, 2013)
Calcifying epithelial odontogenic tumor (CEOT) is a solid, locally aggressive, benign odontogenic neoplasm characterized by sheets and nests of polyhedral epithelial cells exhibiting eosinophilic and less often clear cytoplasm, occasional nuclear pleomorphism without mitotic activity, calcifications, and deposits of amyloid. A cystic variant has been reported only twice. Herein, we present an additional example of cystic CEOT occurring in a 31-year-old male and featuring clear cell epithelial lining with deposits of amyloid and osteodentin.